Bimbingan Konseling Menggunakan Pohon Karir untuk Mengetahui Pemahaman dan Perencanaan Karir Siswa di SMA Swasta Iskandar Paya Gambar - Saida Amini Thasfa; M. Fikri Assidiqie; Ogie Ariansah Pane; Jaka Gunawan; M. Rafli Pasha Handoko; Fanny Arya Rahmasari; Usiono (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The purpose of this service is to determine whether the use of information services based on career trees can improve students' understanding of career planning and to explore ways that educators can Career coaches and counselors will work to prepare students for career growth. The method served by the researchers was qualitative description using the phenomenological approach. The object of this service is guidance and consultation for teachers and students. The results of this service show that high school career guidance determines a student's career choice with the help of media in the form of a career tree that anyone can make using Use existing documents. Because, thanks to the existence of career guidance services, both at the higher level, students can deepen their knowledge about career choices that initially do not have knowledge about career guidance, then receive guidance and advice from lecturers to help students stabilize their lives. their career. choices and the world of work they dream of.